The Dance of Fog: Rewriting Choreographies - Larasati, Rachmi Diyah (IJCAS (International Journal of Creative and Arts Studies), 2024)
This writing is dedicated to the exploration of choreography with specific emphasis on the temporal spatial and references as a historiography and is a method. It centers to memory and temporality that engage with materialism as a trace to embodiment. The objective is to glean inspiration from the story of everyday life, transforming seemingly mundane moments into a moment of creativity for dance the crafting of gestures, and the orchestration of rhythm. Through this artistic process, familiarity and patterns, technique, and emotion, are cultivated and embodied as a historiography method. I argue that embodiment is a transformative journey, leaving imprints on both the body and memory. The Dance of Fog is a choreography that delves into the interplay of value and valuelessness within the archive of embodiment. The inspiration for this exploration is drawn from the correlation between accumulation and poetic interplay of fog, a narrative unfolding to trace the choreographic vagrancy and nuances of dialectic travel memory as politics of witness in conversation with Bethari Uma and Durga the resonance of gender politics in textuality of literary tradition. Tarian “Mega Mendung”: Gubahan dalam Koreografi Abstrak Tulisan ini didekasikan untuk merujuk bagaimana koreografi dituliskan dan dimaknakan dengan menekankan referensi konteks ruang dan waktu sebagai cara melihat kesejarahan dan metode dalam penulisan sejarah. Hal tersebut berfokus pada memori dan temporalitas yang terlibat pada materialisme sebagai cara merunut kebertubuhan dengan tujuan mencatat keseharian dan menggagas bagaimana hal-hal yang duniawi dengan formulasi gerak tari dan pelahiran ritme. Melalui proses kreatif ini, hal yang familiar dan pola— merujuk teknik dan rasa dalam menari, merupakan metode dalam sejarah dan gerakan tubuh menjadi arsip yang hidup. Melalui tulisan ini saya berargumen bahwa kebertubuhan adalah perjalanan yang membawa ilmu perubahan menandai makna dan nilai secara ketubuhan dan memori bukan sebagai nostalgia, akan tetapi sebuah intervensi dalam berfikir. Mega Mendung adalah karya yang merunut pada penentuan sebuah nilai dalam pengarsipan ketubuhan. Inspirasi dari poetika mega mendung (kabut, berawan diambil dari metafora keterhubungan akumulasi dan puitik ruang waktu yang tampak hampa (fog). Koreografi tersebut menggambarkan sebuah kondisi dan ingatan secara dialektika budaya perjalanan sebagai kesaksian dan berdialog dengan politik gender dalam cerita literatur lewat tokoh Dewi Uma, Durga.